The Status and Role of Women In The Society of Nomads In Central Asia - Elmuratovna, Yesimova Anarkul (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The aim of this research is to study the role and status of women in nomadic society, as well as to identify the specifics of the perception of the image of women in traditional philosophical worldview. The attention given to the study of the role of women and their image in philosophy remains of constant interest, as this issue has both ideological and practical significance. In the context of the continuous transformation of modern society’s structure under the influence of various factors, the image of women, their functions, and roles in society are undergoing changes. Primarily, the reasons for the changing image of women include the pragmatization of human relationships, shifts in value orientations, and the increasing complexity of gender and national self-identification processes. The authors identified the significant role of women in nomadic civilization, particularly in the formation and organization of the family and in the upbringing of children. The research also revealed that women of the steppe could participate in crucial decisions concerning their clan and people, as evidenced by the involvement of nomadic women in military battles.The practical significance of this research is determined by the fact that its results can be used in further studies on the role of women in organizing the life of nomads, as well as in research on gender equality. All of the above reflects the relevance of this research and calls for a more comprehensive study of the gender role of women, both in ancient nomadic civilization and in modern society.